Platelet Count and Thrombelastographic Maximal Amplitude in Experimental Thrombocythemias - de Nicola, P (Thrombosis and Haemostasis, 1959)
Experimental thrombocythemias were produced in animals by injecting pantetine, serotonin, progesterone, testosterone, STH, and by carrying out orchid-ectomy. Thrombelastographic determinations of the maximal amplitude were carried out under such conditions and the results correlated with the platelet counts. No significant increases of the maximal amplitude could be observed, even in the presence of very high platelet levels, nor the thrombelastographic signs of a platelet impairment could be detected.